2018
DOI: 10.1002/jcb.27412
|View full text |Cite
|
Sign up to set email alerts
|

Molecular inhibitory mechanism study on the potent inhibitor brigatinib against four crizotinib‐resistant ALK mutations

Abstract: As a potent and selective drug, brigatinib exhibits high efficacy against wild-type and mutant anaplastic lymphoma kinase (ALK) proteins to treat non-small cell lung cancer. In this work, the mechanisms of brigatinib binding to wild type and four mutant ALKs were investigated to gain insight into the dynamic energetic and structural information with respect to the design of novel inhibitors. Comparison between ALK-brigatinib and ALK-crizotinib suggests that the scaffold of brigatinib is well anchored to the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 57 publications
(102 reference statements)
0
3
0
Order By: Relevance
“…Patient with ALK E1129V, F1174C, F1174L, F1174V, I1171T, and G1269A responded to brigatinib lasting 10 months and brigatinib was discontinued when her general condition worsened, at which time liquid biopsy detected the accumulation of EML4-ALK variant 1 and ALK F1174C. ALK F1174C is reported to be resistant to crizotinib but sensitive to brigatinib (6,9). However, we noticed the ALK F1174C might be the resistance mutation of brigatinib.…”
Section: Discussionmentioning
confidence: 78%
“…Patient with ALK E1129V, F1174C, F1174L, F1174V, I1171T, and G1269A responded to brigatinib lasting 10 months and brigatinib was discontinued when her general condition worsened, at which time liquid biopsy detected the accumulation of EML4-ALK variant 1 and ALK F1174C. ALK F1174C is reported to be resistant to crizotinib but sensitive to brigatinib (6,9). However, we noticed the ALK F1174C might be the resistance mutation of brigatinib.…”
Section: Discussionmentioning
confidence: 78%
“…Furthermore, in 2020 it was approved as first-line treatment for ALK-positive metastatic NSCLC patients [100][101][102]. Brigatinib also inhibits ROS1 fusions and EGFR mutation (L858R) and has a remarkable activity on the central nervous system [102,103]. According to the clinical data, brigatinib is active against all the 17 known resistance mutations to the ALK gene, including G1202R and L1196M [104,105].…”
Section: Describing Mechanisms Of Resistance In the First Second And Third Generation Of Alk Tkimentioning
confidence: 99%
“…The S1189C mutation in the ALK kinase domain has not been reported in previous studies, nor is it recorded in any publicly available databases of oncogenes (such as COSMIC and ClinVar). Although brigatinib ( Tu et al, 2019 ), alectinib ( Zhang et al, 2016 ), and lorlatinib ( Syed, 2019 ), as FDA-approved ALK inhibitors, are effective against the F1174L mutation, previous reports have shown that the ALK gene compound mutation is resistant to almost all ALK-TKI inhibitors ( Gainor et al, 2016 ; Takahashi et al, 2020 ; Salifu et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%